Sizing passive filters for mitigation of harmonics in a low voltage network containing solar PV units - Saad T․ Y․ Alfalahi; Muhamad Bin Mansor; Aiman Nouh; Salahuddin I․ Abdrabba; Faisal Mohamed (Franklin Open)
The continual growth of renewables in the distribution scale is converting the conventional arrangement of power grid into a modern arrangement in which the Distribution Generation (DG) units are included within the distribution section of any power system. These renewable units include power electronics-based converters in their construction and the advent of these new technologies deteriorates the Power Quality (PQ) and introduces serious issues of harmonic distortion in both voltage and current waveforms. This research attempts to alleviate the problem of harmonic distortion in low voltage distribution networks containing solar PV modules through the proper sizing of adaptive Passive Harmonic Filters (PHFs). For this purpose, a real distribution network is simulated by ETAP environment, and the harmonic's load flow study is performed to specify the harmonic content at various busbars in the network. Hence PHF models based on the frequency scan performed are proposed to minimize the Total Harmonic Distortion (THD) in the network. The results of the simulations performed have shown that this approach reduces the THD significantly to comply with the permissible limits specified by the international standards IEEE STD 519 and IEC STD 61,000–3–6.